Parental Supervision Strategies for Reducing Gadget Addiction in Elementary Children - Nikmah Hidayatul Khasanah; Dea Rakhimafa Wulandari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rapid technological development has increased gadget use among children, creating risks for academic, social, and physical development. Specific Background: In RT 004, Pesu Village, Magetan, many elementary school-aged children frequently engage in prolonged mobile phone gaming, often with limited parental supervision. Knowledge Gap: Although parents recognize negative outcomes such as addiction, reduced learning focus, and declining social interaction, consistent and firm parental guidance remains insufficiently implemented. Aims: This study aimed to describe the role of parents in addressing the negative impacts of gadget use among SD/MI children in Pesu Village. Results: Using descriptive qualitative methods through observation, interviews, and documentation, findings showed that parental roles were relatively low, despite efforts such as setting time limits, supervising usage, encouraging peer interaction, selecting safe content, modeling responsible gadget behavior, and balancing screen time with other activities. However, inconsistent monitoring and permissive attitudes increased children’s vulnerability to gadget addiction and developmental problems. Novelty: The study highlights specific parental strategies applied within a rural community context where children’s gadget use is socially concentrated and difficult to control. Implications: Strengthening parental consistency, discipline, and cooperation with schools and communities is essential to reduce gadget-related risks and support healthier child development in the digital era. Highlights: Parents applied time scheduling, content selection, and direct monitoring to manage children’s screen habits Inconsistent discipline and permissive practices increased risks of reduced learning focus, social withdrawal, and health complaints Community-based challenges required stronger collaboration between families, schools, and local environments Keywords: Parental Role, Gadget, Technology Addiction.